Phase two exercise rehabilitation following a cardiac event : the effects of group and individual exercise on psychological well-being, physical status and quality of life : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Health Science in Sports and Exercise at Massey University, Wellington, New Zealand - Green, Venessa (Massey University, 2011)
A cardiac event has serious consequences for physical and emotional health. The aim of this research was to determine the effects of a 16 week exercise-based cardiac rehabilitation programme for improving physical status, psychological well-being and quality of life. It also aimed to examine whether group based exercise with social interaction is more beneficial for improving psychological status and quality of life among people undergoing cardiac rehabilitation compared to exercising alone. A pilot study was conducted in 2009 with six participants, all of whom took part in the 16 week programme. Based on this pilot work, a number of modifications were made to the study design, assessments and questionnaires. The main study involved 11 cardiac patients who had all experienced a cardiac event, and were recruited from Wellington Hospital or through word of mouth. The study employed a randomized crossover design, with participants acting as their own controls. The 16 week period was divided into 4x4 week blocks. All participants initially completed a four week baseline condition in the Massey Cardiac Rehabilitation Clinic (standard group exercise activities). Half of the participants then completed one of two intervention conditions, either increased social interaction within group exercise, or individual exercise and minimal social interaction. Following the intervention, participants undertook the 4-week baseline again (to washout intervention effects), and then crossed over to the alternative intervention. On commencing the study and at the end of each 4-week condition, participants completed physical outcome measures (blood sugar and cholesterol levels, performance on the 10m cardiac shuttle test) as well as psychological measures (modified Hospital Anxiety and Depression Scale and SF-36 quality of life questionnaire). Data were analysed using within participant ANOVAs and preplanned t-tests. There were few significant changes across the course of the study. Non-significant trends occurred in the predicted direction for HADS anxiety and depression and for health-related qualify of life in terms of vitality, social functioning, role physical, bodily pain and general health. There was a significant reduction in total cholesterol across the course of the study, while non-significant changes occurred in the predicted direction for diastolic blood pressure (but not for systolic blood pressure or heart rate). As predicted, blood sugar levels decreased over time and improvements on the SWT approached significance (p=.07). Unexpectedly, HDL cholesterol significantly increased and TC/HDL cholesterol decreased across the 16 weeks. Changes in anxiety, depression, and health related quality of life across the two interventions (group/individual) were inconsistent and non-significant, although trends showed improvement in anxiety and depression after the social exercise intervention. Results are discussed in terms of small sample sizes and difficulties in conducting research with cardiac populations. Suggestions for future research are provided, including exploring patients’ perceptions, previous exercise history, support and preference for individual or group-based exercise programmes.
Keywords: Heart diseases; Patients; Rehabilitation; Exercise therapy; Psychological aspects